La atención diferenciada de salud del anciano - Carrasco M., Víctor Hugo (Revista Hospital Clínico Universidad de Chile, 2008)
The world’s population is aging, leading to demographic phenomena hitherto unknown and indeed, different needs for health care, the hitherto prevailing system. Geriatrics is the medical specialty that focuses on overall health care of the elderly, including clinical, mental, social and functional. In Chile is a new discipline, with little more than a decade as a specialty college. His reason for being is that the elderly get sick in a different way, because the manifestations or symptoms of the disease, often have no direct relationship with the organ affected. Moreover, the pathological process may compromise the patient’s autonomy, which often significantly change their future and that of his family. Geriatrics, through a diagnostic procedure and the resulting multidimensional intervention by an interdisciplinary team with varying levels of care, has been shown to improve prognosis and quality of life of many elderly.